Plan estratégico de comunicación para gestión en la comunicación de crisis, resolución de conflictos y comunicación interna de Diario la Hora - Sánchez Borrero, Guillermo Ramón (2015)
The project begins by identifying and justifying the existence of a problem and the urgent need to strengthen the organizational culture to cope with conflicts and crisis in La Hora newspaper, from the force of the Communications Law, to endure over Government media attack through weekly reports in the media of the Government and the entities created as a result of that Law, responsible for regulating and punishing. The document is written in four chapters. The first is a history that demonstrates the problem on a cyclical time of the media sector and the importance it has for society. The second chapter contains an analysis of management theories underlying corporate communication project encompasses three variables: communication in crisis management, conflict resolution and internal communication, such as strengthening the organizational culture to support the moments of crisis...